Keyframe selection for motion capture using motion activity analysis - Kim, Ming-Hwa (2013)
Motion capture data acquired from high definition cameras creates accurate human motion representation but introduces many redundant frames which pose a problem in data storage and motion retrieval purposes. In this paper, a keyframing approach is proposed to reduce the motion data by extracting keyframes using motion analysis approach in sampling windows. Motion changes in sampling windows for original motion without frame skipping and with frame skipping are computed. The difference in the motion changes is the main aspect in deciding whether the frames in sampling windows are possible candidates for keyframe selection. Simulation results showed that the proposed method is able to achieve an overall good visual quality for different types of motion. It also gives an improvement of up to 52% in terms of mean square error measurement, as compared to the existing keyframe extraction method, which is curve simplification method.